The Interaction of Persona, Shadow, and Collective Unconscious in The Short Story of “Harta Ghoib” - Amalia, Dina; Nayla Nurbani Hawa; Mimin Zakiyah; Nur Leli; Rusli (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2026)
This research aims to reveal the psychological condition of characters and society in the short story "Harta Gaib" by Moh Hilmi Faiq through the analytical psychology approach of Carl Gustav Jung. The main focus of the research is to answer the question: How do the interactions between personas, shadows, and collective unconscious shape the behaviors, emotions, and inner conflicts of the characters and the village community? This short story describes the phenomenon of people who are tempted by supernatural treasures, to the point of being willing to commit extreme actions such as pawning rice fields and selling livestock for instant wealth. This study uses a qualitative descriptive method with text analysis, identifying ego manifestations, personal unconscious, collective unconscious, as well as archetypes such as persona, shadow, anima, and self in character behavior and the collective dynamics of society. The results of the study show that Mr. Sobrak builds a manipulative persona to gain the trust of the public, while the collective shadow encourages irrational actions and greed. The collective unconscious arises through the symbolism of treasures and dreams, which affect social interactions as well as the inner conflicts of citizens. This short story not only tells the temptation of instant wealth, but also displays the psychological complexity and collective dynamics of society. This study offers a new perspective on short stories through the lens of Jung's analytical psychology, which was previously rarely used in the analysis of this work.